2010
DOI: 10.1007/s10708-010-9399-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of land use/cover changes and the analysis of landscape fragmentation in Dhaka Metropolitan, Bangladesh

Abstract: Rapid urban expansion due to large scale land use/cover change, particularly in developing countries becomes a matter of concern since urbanization drives environmental change at multiple scales. Dhaka, the capital of Bangladesh, has been experienced break-neck urban growth in the last few decades that resulted many adverse impacts on the environment. This paper was an attempt to document spatiotemporal pattern of land use/cover changes, and to quantify the landscape structures in Dhaka Metropolitan of Banglad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
132
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 212 publications
(136 citation statements)
references
References 54 publications
3
132
0
1
Order By: Relevance
“…The decrease in the LPI and PLAND metrics for forest cover is not surprising because bare land and UPA increased at the expense of natural vegetation (Figure 8). Results from the two dominance indices (LPI and PLAND) at the class level are congruent with Dewan et al's [44] argument that a positive correlation exists between increased human activities and dominance indices. The fragmentation and aggregation indices also support earlier research, which hypothesised that an increase in fragmentation will happen in areas of human habitation because of uncontrolled exploitation of forest resources, especially in settlements triggered by war [11].…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The decrease in the LPI and PLAND metrics for forest cover is not surprising because bare land and UPA increased at the expense of natural vegetation (Figure 8). Results from the two dominance indices (LPI and PLAND) at the class level are congruent with Dewan et al's [44] argument that a positive correlation exists between increased human activities and dominance indices. The fragmentation and aggregation indices also support earlier research, which hypothesised that an increase in fragmentation will happen in areas of human habitation because of uncontrolled exploitation of forest resources, especially in settlements triggered by war [11].…”
Section: Discussionsupporting
confidence: 79%
“…A collection of classes makes up the landscape. Several studies have explored fragmentation at these scales [22,39,[44][45][46]. Exploring the relationship between LULCC, the drivers of change, and the ecological implications of such changes, Kabba and Li [45] concluded that fragmentation at the class and landscape scales in Wuhan, China was greatest in 1987-1994 but weakened in 1994-2005, leading first to species loss in the fragmented areas followed by a return of species as fragmented habitat areas re-aggregated.…”
Section: Landscape Fragmentationmentioning
confidence: 99%
See 3 more Smart Citations